An investigation on the viability and growth characteristics of walliser-schwarzhals and walliser-schwarzhals x hairy goat breeds - Fuat Odabaşıoğlu; Tufan Altın (Eurasian Journal of Veterinary Sciences)
The main animal material of this investigation consisted of 7 Walliser, 17 Hairy goat and 31 Walliser-Schwarzhals x Hairy goat (F-1) crossbreed. Using Walliser and other genotypes, 7 Walliser, 21 F1 and 32 G1 kids were obtained. In this study, viability and growth characteristics of these genotypes have been investigated. In the Walliser, F1 and G1 kids, the percentage of viability was 71, 42 %, 79,16 % and 90,62 % respectively. In the Walliser, F1 and G1 average birth weights were determined as 3.66 ±0.20 kg, 3.46 ±0.11 kg and 3.54 ±0.09 kg respectively. As far as the birth weight is concerned, the difference between genotypes was not statisticaly significant. In the Walliser, F1 and G1 body weights at 12 week were 11.48 ±1.07 kg, 13.02 ± 0.58 kg and 14.58 ± 0.45 kg respectively. The difference between values was found to be significant (P < 0.05) and this variation was due to the difference between Walliser and G1. There was a significant difference between birth types, namely, single kids had more birth weights than twins. An important difference was not found between the sexes. The average daily gain of the body weight in Waliser was 0.094 ± 0.012 kg, in F1 0.113 ± 0.007 kg and in G1 0.131 ± 0.005. Cross-breeds gave far better results than pure breeds with regard to daily average gain of the body weight and 12 week body weight. It was concluded that using Walliser goats as improvers for the hairy goats was more appropriate.